(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sexual crimes against women are on the rise. It has been well documented that sexual assault cases are under reported. The study was conducted in the Department of Forensic Medicine, M.S. Ramaiah Medical College, Bangalore during the period from September 2008 to February 2010, a period of 18 months where in 52 cases were due to sexually related deaths